Barriers to Refactoring. - TEMPERO, EWAN; GORSCHEK, TONY; ANGELIS, LEFTERIS (Communications of the ACM, 2017)
The authors discuss the inability of many computer software developers to refactor software, building on information from computer software developers gathered as part of a 2009 survey. According to the article, reasons for not refactoring include a lack of resources, the risks involved, and a perceived lack of return on investment (ROI).